Accelerated Expansion of Epidermal Keratinocyte and Improved Dermal Reconstruction Achieved by Engineered Amniotic Membrane. Issue 10 (October 2013) - Huang, Guofeng; Ji, Shizhao; Luo, Pengfei; Liu, Houqi; Zhu, Shihui; Wang, Guangyi; Zhou, Panyu; Xiao, Shichu; Xia, Zhaofan
In this study, we used human amniotic membrane (AM) to prepare a dermal scaffold with intact basement membrane (BM) and good biostability for quick expansion and transplantation of epidermal keratinocytes (EKs). Fresh AM was treated by repeated freeze–thaw cycles and DNase digestion. This new method was able to cleanse the cell components effectively and retain the BM structure with continuous distributions of laminin, collagen IV, VI, and VII. Subsequently, the acellular amniotic membrane (AAM) was cross-linked with 1-ethyl-3-(3-dimethylaminopropyl) carbodiimide (EDC) for 5 min, 30 min, and 6 h. With the time of cross-linking prolonging, the mechanical strength and biostability of AAM increased gradually, while its cytotoxicity to EKs also increased. The 5-min cross-linked AAM (5min-AAM) had no significant cytotoxicity with good histocompatibility. The relative cell viability of EKs seeded on the 5min-AAM surface was 367 ± 33% and 631 ± 43% at 7 and 14 days of culture, respectively, both higher than 294 ± 30% and 503 ± 41% of the conventional cell culture dish (CCD) group, and the proportion of P63-positive cells was significantly higher than that of the CCD group on day 7 (54.32 ± 4.27% vs. 33.32 ± 3.18%, p < 0.05). When the 5min-AAM loaded with EKs (EK-AAM) was grafted onto full-thickness skin defects in nude mice, the cells survived well and formed an epidermis similar to normal skin. The new epidermis was thicker, and reconstruction of the dermal structure was good with an intact BM. Four weeks after transplantation, the wound contraction rate in the EK-AAM group was 43.09 ± 7.05%, significantly lower than that in the EK sheet group (57.49 ± 5.93%) and control group (69.94 ± 9.47%) ( p < 0.05). In conclusion, repeated freeze–thaw treatment with appropriate EDC cross-linking offers AAM an intact BM structure with good operability and biostability. It may prove to be an ideal dermal scaffold to promote expansion of EKs in vitro and be transplanted for reconstruction of the dermal structure.